Regeneration of Araucaria angustifolia in three physiognomies of a Mixed Ombrophilous Forest fragment - Valente, Thiago Piazzetta (2010)
It is presented the results of a sudy that evaluated the population structure, dynamics of regeneration, and the infl uence of biotic and abiotic factors over mortality, recruiting and growth of Araucaria angustifolia (Bertol.) Kuntze. The study was conducted in three phytophysiognomies of Mixed Ombrophilous Forest (Mun. São João do Triunfo-PR; 25° 34’ S; 50° 05’ W); representative of distinct successional stages classifi ed according to the intensity of canopy covered by Araucarias. Initially a stable structure (inverted-J) was detected in all three samples surveyed, with high potentials and rates of regeneration. The subsequent monitoring confi rmed this pattern, with high seedling survival and ingress rates being evidenced. A positive relation between the distinct canopy coverings and the natural regeneration rates registered was not detected. However, the populations presented themselves differently when referring to density, mortality and survival, being those determined by a complex web of interactions with the fauna within this ecosystem. Different from older studies, this work emphasizes the existence of a great potential of regeneration for Araucarias inside forests, once the limits of seed harvesting are respected, a non-wood forest product which is widely commercialized in the state of Paraná.